1998
DOI: 10.1590/s1516-31801998000600003
|View full text |Cite
|
Sign up to set email alerts
|

The value of unenhanced CT in the diagnosis of acute appendicitis

Abstract: Unenhanced CT presents a similar overall accuracy to that reported by other authors who studied enhanced CT diagnosis of acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
1
2
0
2
Order By: Relevance
“…9 In our study, the PPV of FACT was 98.9% and NPV was 92.6 %. These results are also supported by other studies which proved positive predictive values of FACT ranging from of 92%-98%, and negative predictive values of 83%-100% 23,24,25 . We found that FACT established an alternative diagnosis in 40 out of total 335 patients (11.9%) with no signs of acute appendicitis on CT. During surgery, no new pathological abnormality was found, and all of the alternative diagnoses were shown to be correct.…”
Section: Discussionsupporting
confidence: 87%
“…9 In our study, the PPV of FACT was 98.9% and NPV was 92.6 %. These results are also supported by other studies which proved positive predictive values of FACT ranging from of 92%-98%, and negative predictive values of 83%-100% 23,24,25 . We found that FACT established an alternative diagnosis in 40 out of total 335 patients (11.9%) with no signs of acute appendicitis on CT. During surgery, no new pathological abnormality was found, and all of the alternative diagnoses were shown to be correct.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, unenhanced CT of the abdomen and pelvis protocol was also used as it can avoid the side effects induced by the contrast medium. Although the unenhanced method can provide the desired accuracy as well, the overall usefulness is still questionable, especially in the cases of children and women [ 145 , 146 , 147 , 148 ]. Interestingly, LDCT has been shown to be comparable to conventional dose CT in terms of clinical outcomes and diagnostic performance [ 149 , 150 ].…”
Section: Imaging Of Gastrointestinal Diseasesmentioning
confidence: 99%
“…Variações nos protocolos foram observadas no estudo de Smith et al (18) , que utilizou técnica convencional em parte dos pacientes e realizou reconstruções com 2 mm de incremento nos exames com técni-ca espiral; no estudo de D'Ippolito et al (3) , cujos exames foram realizados com técnica convencional com cortes contíguos de 8 a 10 mm de espessura; no trabalho de Rao et al (7) , que administrou contraste por via retal (VR) para avaliação de pacientes com suspeita de apendicite aguda; e no trabalho de Sommer et al (19) , que avaliou a utilidade de reconstruções coronais oblíquas e de reformatações multiplanares dos ureteres para avaliar a presença de cálculos.…”
Section: Técnicaunclassified
“…O exame ultra-sonográfico tem sido amplamente utilizado no diagnóstico de apendicite aguda, em virtude do seu baixo custo, da sua grande disponibilidade e por ser inócuo, apresentando sensibilidade e especificidade que variam de 75% a 93% e de 91% a 100%, respectivamente (3,54) . Todavia, trata-se de um método operadordependente, que requer alta capacitação e experiência do examinador, devendo-se salientar ainda a dificuldade do exame em Figura 2.…”
Section: Apendicite Agudaunclassified